Association between Mothersâ Characteristics, Knowledge, Attitude, and Practice and Intestinal Helminthes Infection on Children - Hakiki, Nadhira Permata; Faridah, Lia; Dhamayanti, Meita (Althea Medical Journal, 2016)
Background: The prevalence of soil-transmitted helminthes infection in Indonesia is still high, especially in children aged 3 to 8 years old. Helminthes infection cause loss of nutrition, delay physical development, intelligence, and labor productivity and decrease immunity. Mothersâ characteristics, knowledge, attitude, and practice are some of the factors that influence the occurrence of intestinal helminthes infection on children. This study was aimed to find the association between mothersâ characteristics, knowledge, attitude, and practice and the occurrence of intestinal helminthes infection on children.Methods: The study was conducted at Jatinangor Cohortâs research center from August to September 2014 using cross sectional analysis. One hundred and forty five secondary data were collected using validated questionnaire that filled by mothers and results of feces on children were tested. The amount of data excluded due to incomplete was 8, the data utilized was then analyzed by Chi Square evaluation.Results: Mothersâ characteristics such as age (P = 0.611), education (P = 0.952), occupation (P = 0.876), income (P = 0.199), and knowledge (P = 0.424; OR = 1.333), attitude (P = 0.236; OR = 0.808), practice (P = 0.333; OR = 4.625) did not have a significant association with the occurrence of intestinal helminthes infection on children.Conclusions: Characteristics, knowledge, attitude, and practice of the mothers towards the intestinal helminthes infection do not associate with the occurrence of intestinal helminthes infection on children. [AMJ.2016;3(2):248â53]Â DOI:Â 10.15850/amj.v3n2.794